The Effect of Risk Management and Profitability on Stock Prices Moderated by Good Corporate Governance Variables - Zulfitra Zulfitra; Yulian Bayu Ganar; Sahroni Sahroni; Muhammad Abiyyu Arsyan (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
The purpose of this study was to examine the Effect of Risk Management and Profitability on Stock Prices moderated by Good Corporate Governance (a case study of companies indexed LQ 45 for the period 2017-2021). The method used in this study is a quantitative descriptive method. The data analysis technique used descriptive statistical analysis, panel data regression analysis, classical assumption test. Hypothesis testing includes statistical t test and f test, as well as testing the coefficient of determination using Eview 12 software. The results show that partially Enterprise Risk Management and Gross Profit Margin have a positive and significant effect on stock prices, while Return of Assets has no effect on stock prices. . Good Corporate Governance strengthens the relationship between Enterprise Risk Management, Gross Profit Margin with stock prices and Good Corporate Governance weakens the relationship between Return of Assets and stock prices. Simultaneously the variables Gross Profit Margin, Total Assets Turn Over, Return On Investment, and Good Corporate Governance have a positive and significant effect on stock prices.